Two new records of hippolytoid shrimps, Lysmata hochi Baeza & Anker, 2008 (Decapoda: Lysmatidae) and Lysmata amboinensis (de Man, 1888) from Lakshadweep Islands, India with taxonomic notes - Jose, Sheena; Purushothaman, P.; Madhavan, Manu; Akash, S.; Bharathi, S.; Dhinakaran, A.; Kumar, T.t. Ajith; Lal, K. K. (Zootaxa, 2020)
The present study reports the new records of two species of the hippolytid shrimp genus Lysmata Risso, 1816 in the water off Lakshadweep Islands, India from the Arabian Sea, viz. Lysmata hochi Baeza & Anker, 2008 and Lysmata amboinensis (De Man, 1888) with more taxonomic information. Moreover, L. hochi is the first distributional report from the Indian Ocean. It is morphologically similar to L. kuekenthali and differences are discussed. Colour pattern and morphological trait of L. amboinensis are very close to L. grabhami which also differs in the presence of anti-penultimate segment of 3rd maxilliped more than 2.0 times as long as penultimate segment and stylocerite does not reaching the distal end of the cornea. These specimens were obtained at a depth of 0.5-2 m from the intertidal region of Agatti Island. Additionally, we estimated pairwise genetic distances for these two species and congeneric species using cytochrome oxidase subunit I gene sequences where interspecific distances ranged from 11-25.8 %.